2007
DOI: 10.1177/0011392107073299
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Age and Gender

Abstract: This article discusses the position of older women in gender theory and in social gerontology. It shows how older women are made invisible in gender theory through the selection of arenas and themes, by model monopoly and by a lack of problematization of age. In the social gerontological field, older women have frequently been objects of research. However, double jeopardy assumptions have resulted in a perspective that foregrounds misery. Results from focus group interviews with women aged 75 and over, shed li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(59 citation statements)
references
References 28 publications
2
45
0
12
Order By: Relevance
“…This might be due to the higher awareness and sensitivity to social inequality issues sometimes attributed to women (Palmore 2001). At the same time, these results confirm the vast literature on ''double jeopardy'' or ''gendered ageism'' experienced by women, where two types of discrimination, based on age and gender, can be intertwined and strengthen each other (Krekula 2007;Macnicol 2006;Sontag 1972;Walker et al 2007). However, when checked for other variables, gender differences remained significant only in the case of hard discrimination.…”
Section: Discussion Hard and Soft Discriminationsupporting
confidence: 76%
See 1 more Smart Citation
“…This might be due to the higher awareness and sensitivity to social inequality issues sometimes attributed to women (Palmore 2001). At the same time, these results confirm the vast literature on ''double jeopardy'' or ''gendered ageism'' experienced by women, where two types of discrimination, based on age and gender, can be intertwined and strengthen each other (Krekula 2007;Macnicol 2006;Sontag 1972;Walker et al 2007). However, when checked for other variables, gender differences remained significant only in the case of hard discrimination.…”
Section: Discussion Hard and Soft Discriminationsupporting
confidence: 76%
“…As plethora of studies showed age discrimination more often affects women (Duncan and Loretto 2004;Krekula 2007;Lincoln and Allen 2004) and persons of lower educational attainment (van den Heuvel and van Santvoort 2011). Ageism operates also differently across the life course (Bytheway 2005).…”
Section: Explaining Age Discrimination: Socio-demographic and Occupatmentioning
confidence: 99%
“…Although research on men's embodiment is now growing, the study of masculinities as men age remains in its infancy (Calasanti 2010, Tarrant 2014, Thompson 2007. Originating within feminist gerontology, a limited body of work has theorised age and gender as intersecting processes (Calasanti 2005, King and Calasanti 2013, Krekula 2007, Tarrant 2014. Studies have explored commonalities in men's ageing such as grandfatherhood (Scraton and Holland 2006), widowhood (Bennett 2007) and the provision of spousal care (Russell 2007), yet the embodiment of gender and ageing within chronic illness remains under-studied (Hurd Clarke andBennett 2013, McVittie andWillock 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This fleshy, social body is central to the understanding of subjectivity in, for example, phenomenology, feminist studies, and postphenomenology. Subjectivities are embodied in the materiality of the body (the flesh), and bodies are embedded in relation to other bodies and the world (the social) [24, 2931]. Subjectivity/identity is made possible precisely by the intercorporeal connections that all human beings sustain with each other [30].…”
Section: Ageing Bodies As “Social Flesh”mentioning
confidence: 99%